Knowledge, attitude and practice towards cervical cancer screening and human papilloma virus vaccine at a tertiary care facility in North India - Misra, Devyani; Mahajan, Charu; Bansal, Bhumika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical cancer continues to be a major health care problem and most common cause of cancer deaths. Many screening methods are available to detect the disease in precancerous stage. Cervical cancer is the only cancer that is preventable with HPV vaccine against the causative agent responsible for this condition. Knowledge and attitude of women determine the likelihood of women undergoing screening procedures and HPV vaccination which will have implications for the future generations. This study was conducted to determine the knowledge, attitude and practice of women towards cervical screening and HPV vaccine. Methods: This is a facility based observational cross-sectional study conducted at Dr. RMLIMS, Lucknow, over a period of 3 months - January 2019 to March 2019. Women attending gynecology OPD were enrolled after verbally consenting for the study and were required to fill a pre-structured questionnaire which was then analyzed and assessed. Results: A total of 368 participants answered the questionnaire. Overall, 154 subjects (41.8%) had adequate knowledge regarding cervical carcinoma risk factors, symptoms, screening for cancer and HPV vaccine. Favorable attitude was seen in 315 (85.5%) participants. Ninety-six participants (26.0%) had ever had a cervical cancer screening and 23 participants (6.2%) had ever received HPV vaccine which was very low. Lack of knowledge and cost factors were the main reasons cited for these low screening and vaccination rates among the participants. Conclusions: The study shows that knowledge was inadequate and screening and vaccination rates were very low in the study population. This highlights the need to educate the community regarding cervical cancer prevention and to make these services readily available at affordable costs to achieve the ultimate goal of elimination of cervical cancer.